Optimasi Produksi Gaultherin Dari Gandapura Dengan Teknologi Mixed-Drying Extraction - Priyono Kusumo (Jurnal Teknik Industri, 2014)
This study purposed the optimization of gaultherin production from “gandapura” by inactivating the gaultherase enzyme, including gaultherin productivity and process parameters. This research applied the combination processes of extraction-dryer, simultanously. The productivity of gaultherin was improved by adding the drying agent, such as magnesium sulfate, sodium sulfate, calcium chloride, and calcium sulfate. The optimization was conducted using a factorial design 2n. Dependent variables determined by calculating the main effects and interactions, following by the application of probability plots. During the research, the content of gaultherin, methyl salicylate, salicylic acid were measured by using a spectrophotometer and HPLC-MS. The results shows that the higher concentration of drying agent (especially calcium chloride) and ethanol, increased the content of gaultherin. However, the most influenced factor to this conducted process was pH, regarding to the concentration of ethanol. During extraction, the higher the pH, increased the active compound of gaultherin. The optimum condition of enzyme inactivation was found at pH 8 with the content of gaultherin at 14.46%. The higher the solvent concentration of ethanol, the higher content of gaultherin can be extracted. The maximum process condition regarding to ethanol concentration found at 90% with active compound concentration at 13.10%.